Lunasin protease inhibitor concentrate decreases pro-inflammatory cytokines and improves histopathological markers in dextran sodium sulfate-induced ulcerative colitis - Andrea Nieto-Veloza; Zhihong Wang; Qixin Zhong; Doris D’Souza; Hari B. Krishnan; Vermont P. Dia (Food Science and Human Wellness)
Lunasin protease inhibitor concentrate (LPIC) is a novel combination of soy bioactive peptide lunasin, Kunitz and Bowman-Birk protease inhibitors. The reported anti-inflammatory and anticancer properties of each one of them suggest LPIC as a promising candidate for the treatment of inflammatory-related diseases. Our objective was to assess the in vivo anti-inflammatory properties of LPIC. First, an in vitro test was performed in lipopolysaccharide (LPS)-activated RAW264.7 murine macrophages by measuring the production of nitric oxide (NO), interleukin-6 (IL-6), and tumor necrosis factor α (TNF-α) as inflammatory markers. For the in vivo model, ulcerative colitis (UC) was induced in mice via oral administration of dextran sodium sulfate (DSS). LPIC treatment was performed via daily intraperitoneal injection of 50 mg/kg body weight. Body weight, visible blood in stool and stool consistency were scored daily as macroscopic indicators of disease progression. Occult blood was evaluated by the presence of hemoglobin in stool every third day. Colon length, caecum weight, colonic myeloperoxidase activity (MPO), presence of pro-inflammatory cytokines in blood and colon, changes in the architecture, and expression of inducible nitric oxide synthase (iNOS) in colonic tissue were evaluated. In vitro, LPIC induced production of NO and maintained cytokine levels in comparison to activated untreated macrophages. In vivo, LPIC increased colonic bleeding and did not improve macroscopic markers of the disease, but reduced colonic IL-1β and IL-6, decreased systemic circulation of TNF-α, attenuated neutrophils infiltration and iNOS expression in colonic tissue, and diminished the damage in colonic architecture. Our results suggest that combinations of peptides in LPIC may counteract the anti-inflammatory properties in vitro; while in vivo, LPIC can significantly reduce the histopathological damage, hence is a possible therapeutic strategy to attenuate UC.